HUBUNGAN ANTARA INTENSITAS BERMAIN GADGET DENGAN KEMAMPUAN PRAGMATIK ANAK UMUR TIGA SAMPAI ENAM TAHUN DI TK TUNAS RIMBA GUNDIH KECAMATAN GEYER KABUPATEN GROBOGAN - Mustikasari, Dian; Anisyah Dewi Syah Fitri (Tahta Media Group, 2022)
Background: According to Santoso (2013), Gadgets are used regularly excessive and uncontrolled can have bad consequences in terms of psychology and children can not socialize or communicate in the surrounding environment smoothly. According to Kridalaksana (2018), Pragmatics is defined as the conditions that result in the use of language in communication being compatible or not, aspects of language use or the external context of language that contribute to the meaning of utterances. Objective: This study aims to determine whether there is a relationship the intensity of playing gadgets and the pragmatic abilities of children aged three to six years at Tunas Rimba Gundih Kindergarten, Geyer District, Grobogan Regency. Methods: This research is a quantitative research with an associative approach. The sample size used was 32 respondents. data that accumulated was tested using Spearman's rho. Research Results: The results of Spearman's rho test results obtained Sig. 0.000, where the significance value is less than 0.005 with the Correlation Coefficient or the strength of the correlation coefficient of -0.798. So the alternative hypothesis (Ha) accepted that there is a relationship between the intensity of playing gadgets with pragmatic ability, with very strong accuracy. Conclusion: There is a negative relationship between the intensity of playing gadgets and the pragmatic abilities of children aged three to six years at Tunas Rimba Gundih Kindergarten, Geyer District, Grobogan Regency. This negative direction has meaning, the higher the intensity of playing gadgets, the more disturbed the development of children's pragmatic abilities, and vice versa.